2020
DOI: 10.1093/cdn/nzaa141
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Updating the Minimum Dietary Diversity for Children Indicator for Tracking Progress in the Eastern and Southern Africa Region

Abstract: Minimum Dietary Diversity (MDD), a population-level dietary quality indicator, is commonly used across low- and middle-income countries to characterize diets of children age 6–23 months. World Health Organization (WHO) and United Nations Children's Fund (UNICEF) recently updated the MDD definition from consumption of ≥ 4 of 7 food groups in the previous 24 hours (MDD-7) to ≥ 5 of 8 food groups (MDD-8), adding a breastmilk group. The implications of this definition change were examined across 14 countries in Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…The study, however, had several limitations. First, minimum dietary diversity was defined as the proportion of children aged 6–23 months who consumed ≥4 of 7 food groups (minimum dietary diversity—7) in the previous 24 h instead of ≥5 of 8 food groups (minimum dietary diversity—8) in the previous 24 h as reported [ 62 ], but a current study that examines minimum dietary diversity in eastern and southern African regions indicated that confidence intervals for prevalence estimates regarding minimum dietary diversity—7 and minimum dietary diversity—8 overlapped in most eastern and southern African countries [ 63 ]. Second, this study did not consider the new IYCF indicators such as mixed milk feeding, sweet beverage consumption, unhealthy food consumption, and zero vegetable or fruit consumption, which was reported in the 2020 IYCF indicators [ 62 ], Third, several discussed factors associated with IYCF practices may differ for adolescent and adult mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The study, however, had several limitations. First, minimum dietary diversity was defined as the proportion of children aged 6–23 months who consumed ≥4 of 7 food groups (minimum dietary diversity—7) in the previous 24 h instead of ≥5 of 8 food groups (minimum dietary diversity—8) in the previous 24 h as reported [ 62 ], but a current study that examines minimum dietary diversity in eastern and southern African regions indicated that confidence intervals for prevalence estimates regarding minimum dietary diversity—7 and minimum dietary diversity—8 overlapped in most eastern and southern African countries [ 63 ]. Second, this study did not consider the new IYCF indicators such as mixed milk feeding, sweet beverage consumption, unhealthy food consumption, and zero vegetable or fruit consumption, which was reported in the 2020 IYCF indicators [ 62 ], Third, several discussed factors associated with IYCF practices may differ for adolescent and adult mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the validation work related to the child MDD indicator to date has focused on its ability to serve as a proxy for nutrient adequacy ( 27 , 28 ). Subsequently, refinement of the indicator from a 7-item to an 8-item score including breast milk took place to improve its utility as a more comprehensive indicator of children's diets during the 6- to 23-mo period ( 10 , 11 ). However, even though patterns in food insecurity and food availability are known to be seasonal in many rural contexts, we believe that this is the first study to examine the seasonality of the MDD indicator from the perspective of understanding its validity for monitoring high-level changes in diet quality over time (i.e., the type of monitoring done by UN agencies, governments, and global accountability initiatives).…”
Section: Discussionmentioning
confidence: 99%
“…MDD is a core indicator in the WHO Global Nutrition Monitoring framework, and national estimates are tracked over time for all WHO member states ( 9 ). Many low- and middle-income countries (LMICs) have set national and subnational targets for MDD related to reducing the proportion of children with a low MDD or minimum acceptable diet (MAD), an indicator derived in part from MDD ( 10 ). Country profiles for the Global Nutrition Report, a global nutrition accountability report, include both MDD and MAD ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the trends and determinants of dietary diversity may help explain the progress towards global infant and young child nutrition targets, thus improving the design of programme interventions (19) . Moreover, it is critical to conduct a study using the MDD-8 indicator due to the country's transition to the new measure and the need for a valid interpretation of dietary diversity trends and determinants (12) . Thus, this study aimed to examine the trends and determinants of MDD-8 among children aged 6-23 months using nationally representative data collected from the 2007, 2012 and 2017 IDHS.…”
mentioning
confidence: 99%